The Influence of Human Resources Quality and Work Motivation on Employee Performance At PT. JNE Express Medan Main Branch - Nora Sastia (Cattleya Darmaya Fortuna, 2022)
Companies are experiencing the complexity of the increasing high competition in the industrial world, so companies are required to improve employee performance. Employee performance is influenced by various factors, namely the quality of human resources and work motivation, at PT. JNE EXPRESS Main Branch Medan is known that the employee's performance is categorized as inadequate, reflected in the low level of discipline in working time, the ability to complete tasks not in accordance with the specified target, and there are still employees who are not satisfied with their level of quality. This study aims to determine the effect of the quality of human resources and work motivation on employee performance at PT. JNE EXPRESS Main Branch Medan. This study examined as many as 81 respondents as the research sample. Sampling was done by probability sampling and using simple random sampling. The data analysis method used is the quantitative analysis method with an associative approach, which includes validity test, reliability test, normality test, multiple linear regression test, t test, f test, and coefficient of determination test. The test was carried out using the help of SPSS v.2.0 The results showed that the variable quality of human resources had a significant effect on employee performance based on the acquisition of a tvaluecount of 1.363 1.664 with a significance level of 0.177 > 0.05. The work motivation variable has a significant effect on the performance of employees, based on the acquisition value of tcount equal to 2,543 > 1,664 with a significance level of 0.13 > 0.05. seen from the coefficient of determination Rvalue2 of 0.424, which means that the effect of quality and work motivation on employee performance at PT. JNE EXPRESS is 18% while the remaining 82% is influenced by other variables not included in this study